The maize gene ZmSBP17 encoding an SBP transcription factor confers osmotic resistance in transgenic Arabidopsis - Sun, Lifang; Wang, Lijiao; Niu, Jinping; Yang, Wei; Li, Zhifang; Liu, Libin; Gao, Shuren (Frontiers in Plant Science, 2024)
Among the major abiotic stresses, salt and drought have considerably affected agricultural development globally by interfering with gene expression profiles and cell metabolism. Transcription factors play crucial roles in activating or inhibiting the expression of stress-related genes in response to abiotic stress in plants. In this study, the Zea mays L. SQUAMOSA promoter-binding protein gene (ZmSBP17) was identified, and the molecular regulatory mechanism of osmotic stress tolerance was analyzed. Phylogenetic analysis confirmed that ZmSBP17 is part of the SBP gene family and is closely related to OsSBP17. The ZmSBP17-GFP fusion protein exhibited green fluorescence in the nucleus, as determined via tobacco epidermal transient transformation system. Acting as a transcriptional activator, the overexpression of ZmSBP17 in Arabidopsis significantly enhanced the expression of genes encoding superoxide dismutases (CSD1/2, MSD1), catalases (CAT1/2), ascorbate peroxidase 1 (APX1), and myeloblastosis transcription factors (AtMYB53/65), which increased the activity of reactive oxygen species (ROS)-scavenging enzymes and reduced ROS levels. Additionally, the expression of abiotic stress-related genes, such as AtDREB2A and AtNHX1, was significantly upregulated by ZmSBP17. Furthermore, ZmSBP17 specifically bound to cis-acting elements containing GTAC core sequences in the promoters of stress-related genes, suggesting that ZmSBP17 regulates the transcription of certain genes by recognizing these sequences. These results indicate that the overexpression of ZmSBP17 in Arabidopsis thaliana significantly increased tolerance to osmotic stress during the germination and seedling stages, which may enhance our understanding of the biological functions of SBPs in maize under abiotic stresses.